2019
DOI: 10.3389/fncel.2019.00133
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Secreted α-Klotho in the Hippocampus Alters Nesting Behavior and Memory Formation in Mice

Abstract: The klotho gene family consists of α-, β-, and γ-Klotho, which encode type I single-pass transmembrane proteins with large extracellular domains. α-Klotho exists as a full-length membrane-bound and as a soluble form after cleavage of the extracellular domain. Due to gene splicing, a short extracellular Klotho form can be expressed and secreted. Inactivation of α-Klotho leads to a phenotype that resembles accelerated aging, as the expression level of the α-Klotho protein in the hippocampal formation of mice dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 76 publications
0
20
0
1
Order By: Relevance
“…Dubal et al (2015) also showed that Klotho elevation in hAPP/KL mice increased NMDAR‐dependent long‐term potentiation (LTP) despite of not altering hippocampal levels of Aβ. Li et al (2019) found that secreted human Klotho altered some synaptic plasticity‐related proteins and mediated a significant increase in fEPSP slope per unit of stimulation intensity in mice. These results showed the direct regulation of Klotho itself on synaptic plasticity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Dubal et al (2015) also showed that Klotho elevation in hAPP/KL mice increased NMDAR‐dependent long‐term potentiation (LTP) despite of not altering hippocampal levels of Aβ. Li et al (2019) found that secreted human Klotho altered some synaptic plasticity‐related proteins and mediated a significant increase in fEPSP slope per unit of stimulation intensity in mice. These results showed the direct regulation of Klotho itself on synaptic plasticity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact function of Klotho in the central nervous system (CNS) is not known, it has been shown to enhance N-methyl-D-aspartate receptor (NMDAR)mediated synaptic activity [12] and oligodendrocyte maturation [8]. Furthermore, Klotho has been shown to regulate hippocampal synaptic plasticity [12,26,28]. Thus, it is conceivable that ablation of C9orf72 alters the Klotho expression and affects Klotho-mediated regulation on synaptic plasticity.…”
mentioning
confidence: 99%
“…KL knockout mice show elevated levels of proinflammatory factors and macrophage infiltration in the choroid plexus [ 32 ]. Overexpression of the secreted form of KL in the hippocampus reverses aging-related effects and cognitive dysfunction in mice [ 33 ]. Thus, KL potentially represents a protective or therapeutic target for hippocampal or cognitive dysfunction following noise-induced hearing loss.…”
Section: Discussionmentioning
confidence: 99%